Dynamics of Weakness and Strength: Confronting Difficulties in The Bamboo Stalk. - yasir, maha (Thi Qar Arts Journal, 2024)
This paper will critically discuss the Dynamics of Weakness and Strength with and overcomes the problems that naturally paper from being of Kuwaiti-Filipino heritage. The study aims to portray the dynamics of weakness and strength in Confronting and to show how they have an impact on his identity development and the sense of belonging Difficulties in "The Bambo Stalk" by Saud Alsanousi. Being revealed in such a way are intricate dynamics of weakness and strength along José’s trajectory, and the study adds to discourses of cultural identity, resilience, and the complexities of multiculturalism in literature, which have lots to give for understanding the struggle of individuals with mixed heritage in today’s societies. The analysis points out that In the novel "The Bamboo Stalk," Saud Alsanousi tells José’s coming-of-age story against the backdrop of societal prejudice and cultural clashes, evidencing both his strength and times of weakness. Through this narrative, he reveals man’s struggle for acceptance and belonging. José’s story becomes, therefore, an intense search for identity in a world ruled by social norms and biases at the end.